Individuo, relazione, comunità - Botturi, Francesco (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
The relationship-community nexus is a hermeneutical key to issues of abso-lute speculative importance and of pressing topicality. Hence the interest in this theme, which has many profiles, including: the question of the opposite presupposition, that of individualism; the statute of anthropological relationality; the communitarian media-tion of the social. Here I would like to propose the salient points of a possible itinerary in this area of questions.